Colloids for Nano- and Biotechnology - Hórvölgyi, Zoltán.; Hórvölgyi, Zoltán.; Kiss, Eva.; Kiss, Eva. (Progress in Colloid and Polymer Science,, 2008)
This volume contains a selection of the papers presented at the 9th Conference on Colloid Chemistry. A colloid chemical approach to nano- and biotechnology was one of the main topics of the meeting held in Siófok, Hungary in October 2007. It was organized by the Hungarian Chemical Society in cooperation with leading Hungarian universities and the Hungarian Academy of Sciences. The contributions demonstrated the progress of the field and supported that "The world of neglected dimensions" should not be neglected at all in modern material sciences and technologies. This volume is intended for professionals dealing with fundamental research or development of industrial applications, who encounter colloids, nanostructures, and interfacial phenomena during their work.